Use of IAEA's phase-space files for virtual source model implementation: Extension to large fields. Issue 8 (August 2016) - Rucci, Alexis; Carletti, Claudia; Cravero, Walter; Strbac, Bojan
Highlights: IAEA's phase-space files are used to build a photon beam virtual source model. The model was extended to large fields adding a virtual flattening filter. This virtual source model could be used as a TPS verification system. Abstract: In a previous work, phase-space data files (phsp) provided by the International Atomic Energy Agency (IAEA) were used to develop a hybrid virtual source model (VSM) for clinical photon beams. Very good agreement with dosimetric measurements performed on linear accelerators was obtained for field sizes up to 15 × 15 cm 2 . In the present work we extend the VSM to larger field sizes, for which phsp are not available. We incorporate a virtual flattening filter to our model, which can be determined from dose measurements for larger fields. In this way a fully functional VSM can be built, from publicly available IAEA's phsps and standard dose measurements, for fields of any size and tailored to a particular linac.